2017
DOI: 10.1111/afe.12274
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grapevine bunch exposure to sunlight on berry surface temperature and Lobesia botrana (Lepidoptera: Tortricidae) egg laying, hatching and larval settlement

Abstract: 1 Bunch-zone leaf removal reduced infestation by Lobesia botrana, although the mechanism responsible for this effect is unknown. 2 Based on the mortality of eggs and newly-hatched larvae exposed to high temperatures (≥37 ∘ C) in the laboratory, the present study aimed to assess the influence of (i) bunch-zone leaf removal and grapevine-row orientation on berry surface temperature and (ii) bunch exposure to sunlight on egg and larval mortality. 3 Berry temperatures were measured using a noncontact infrared ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…In the laboratory, sulfur dust reduced the preference of L. botrana larval settlement in line with the results obtained for T. absoluta [ 43 ], but in this earlier study the effect was stronger (around 90% compared to 55%). The deterrent effect of sulfur dust on the larvae, markedly observed in the laboratory, could also occur in the field and hinder the penetration of the berries by the newly hatched larvae, which, when remaining longer on the skin of the grapes, could be more exposed to the abiotic and biotic factors of mortality [ 21 ]. The prolonged wandering time of the newly hatched larvae could also increase the efficacy of insecticides active exclusively or predominantly before the larvae penetrate the berries (e.g., B. thuringiensis, indoxacarb), lengthening the period in which they can be in contact with or feed on the skin of the berries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the laboratory, sulfur dust reduced the preference of L. botrana larval settlement in line with the results obtained for T. absoluta [ 43 ], but in this earlier study the effect was stronger (around 90% compared to 55%). The deterrent effect of sulfur dust on the larvae, markedly observed in the laboratory, could also occur in the field and hinder the penetration of the berries by the newly hatched larvae, which, when remaining longer on the skin of the grapes, could be more exposed to the abiotic and biotic factors of mortality [ 21 ]. The prolonged wandering time of the newly hatched larvae could also increase the efficacy of insecticides active exclusively or predominantly before the larvae penetrate the berries (e.g., B. thuringiensis, indoxacarb), lengthening the period in which they can be in contact with or feed on the skin of the berries.…”
Section: Discussionmentioning
confidence: 99%
“…In the vineyard, a standard fungicide program was followed and a single application of acetamiprid (Epik, Sipcam, Milano, Italy) for the control of the leafhopper Scaphoideus titanus Ball (Hemiptera: Cicadellidae) was carried out on 20 June, i.e., almost two months before the beginning of the bioassays. Shoots holding two bunches of similar size and not in contact with each other were chosen [ 21 ]. Bunches were checked for the absence of L. botrana eggs before starting each bioassay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with these considerations, the higher residual efficacies obtained in the semi-field than in field conditions could be due not only to a better coverage by the insecticide solution, but also by the lower temperatures experienced due to the shading net. In fact, leaves exposed to sunlight can have a temperature even 5 degrees higher than shaded ones [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the maximum three-day difference in larval development time among cultivars reported in this last study does not seem sufficient to explain the differences in larval age composition observed in the field (data reported in [ 21 ] and in this study) because the interval between the two moultings is around a week. The differences in larval development time among cultivars could also be due to berry temperature, which is related to different amounts of sun exposure on bunches [ 20 , 36 , 37 ]. On the other hand, regarding the hypothesis that cultivar affects egg-laying periods, there is no evidence to suggest that females at the beginning of their oviposition period lay more eggs on berries of certain cultivars.…”
Section: Discussionmentioning
confidence: 99%